From poor state to rich state: How long does it take? - Habibullah, Muzafar Shah; Sanusi, Nur Azura; Abdullah, Lazim; Kusairi, Suhal; Golam Hassan, Asan Ali; Ghazali, Normi Azura (2015)
The objective of the present paper is to address the question whether the less developed states, namely; Kedah, Kelantan, Pahang, Perlis, Sabah, Sarawak and Terengganu are catching-up with the more richer state of Selangor, using the generalized one-step error-correction model for the period 1970-2013.We tested convergence on real GDP and per capita real GDP for the states involved and the results suggest that the less developed states has been converging to the state of Selangor for the period under study. In this study, we also determine the time required for the less developed states to converge to the level of economic development of Selangor.In terms of real GDP, the less developed states will take longer to converge to the state of Selangor, however, in terms of per capita real GDP, the less developed states can converge at a faster rate to the level of economic development of Selangor if these states can grow more than double than the growth in Selangor.In this respect, the state government has an important role to play in enhancing growth by continuously providing stable economic environment for investment and other productive economic activities. This will ensure full convergence can take place at a faster rate in the future.